Wide band gap semiconductor nanowires. - Consonni, Vincent; Feuillet, Guy (Electronics engineering series (London, England), 2014)
This book, the second of two volumes, describes heterostructures and optoelectronic devices made from GaN and ZnO nanowires. Over the last decade, the number of publications on GaN and ZnO nanowires has grown exponentially, in particular for their potential optical applications in LEDs, lasers, UV detectors or solar cells. So far, such applications are still in their infancy, which we analyze as being mostly due to a lack of understanding and control of the growth of nanowires and related heterostructures. Furthermore, dealing with two different but related semiconductors such as ZnO and.